The Application of Music Therapy For Children with Autism Based On Facial Recognition Using Eigenface Method - Yusufiyah, Hesti Khuzaimah Nurul; Usuman, Ilona; Putra, Agfianto Eko; Widodo, Triyogatama Wahyu (Faculty of Science and Technology, State Islamic University Walisongo Central Java, 2017)
This research is motivated by the condition of children with autism who require continuous monitoring without a parent accompany, and certain therapies who is capable to reduce repetitive behaviors and increase the concentration. Music therapy is one of the treatment which able to perform it. The implementation of this research is located in a special schools with autism, the perform is proper at certain times and requires tools for music therapy. Therefore, the integrated device was made to monitor the activities of children with autism, as well as providing music therapy automatic face recognition based on Eigenface method.This device perform when the children with autism under certain conditions (e.g. crying, the teacher would not work orders, etc.), then by capturing the the facial image, the system will process to compare the similarity with the existing database. Then, the shortest distance of euclidean is chosen. If the captured of facial image is similar to the one existing database, then the music is performed as music therapy for children with autism. The results of this system, indicates that the childs responses become more calm, easy concentration, and the repetitive attitude is reduced. While the accuracy of the system achieves by 80% (compare with the old and new database) and 20%. (without new database). Â©2017 JNSMR UIN Walisongo. All rights reserved.